Analysis Systems of Aftercooler on Bulldozer D375A-6R - Hasan Basri; Jaref Darmawan; Ery Diniardi; A I Ramadhan; Firmansyah Firmansyah (Faculty of Engineering Universitas Muhammadiyah Jakarta, 2020)
The bulldozzer is seen as the most efficient heavy equipment unit for mining, specifically dozzing and ripping material. The purpose of this study was to analyze damage due to cracks in the cooler afterwards which caused dust and dirt to enter the air intake system which caused excessive piston, piston ring and cylinder wear liners in the Bulldozer. The research method was conducted using 8-step troubleshooting analysis. The results and discussion are damage due to cracks in the after cooler which causes dust and dirt into the air intake system which causes the piston, piston ring and cylinder liner to wear out excessively. The piston, piston ring and cylinder liner have excessive scratching and wear, so the compression pressure that should be compressed inside the combustion chamber experiences a leak where the air enters the crankcase chamber.